Antibiotic residues in farmed raised tilapia (Oreochromis niloticus) of southwest region of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The objectives of this investigation were to seek out the residue level of nitrofurans and chloramphenicol in cultured tilapia muscle in south west region of Bangladesh. Ninety samples were collected randomly from various fish farm of different Upazillas of Khulna, Satkhira and Bagerhat districts during August-December, 2017, where each district was contained 30 samples. Antibiotic residues level present in the animal muscles were detected using ELISA in the Quality Control Laboratory of the Department of Fisheries, Khulna, Bangladesh. To collect information about the status of feed type questionnaire interviews were performed during sample collection from the respective farmers. The overall results revealed that nitrofuran metabolites and CAP residue existed in all the samples within the MRL (Maximum Residue Level) with the exception of 3.33%, 6.66% and 3.33% samples of Khulna, Bagerhat and Satkhira district respectively. Antibiotic residue data showed all nitrofuran metabolites like SEM, AOZ, AMOZ, AHD and CAP were present in all samples in which SEM was highest in Shatkhira district and lowest in Khulna district. In case of AHD, highest residue was found in Khulna and lowest was Satkhira district. Additionally, AOZ was highest in Khulna district and lowest in Bagerhat district and AMOZ was highest in Bagerhat district and lowest Satkhira district. CAP was found highest in Satkhira district while that was lowest in Bagerhat district. The results of the also revealed that contamination of nitrofuran metabolites and chloramphenicol were more in tilapia farms where home-made feed was used compared to commercial feed.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 102-108